A multi-limb coordination approach to front crawl - Shemeikka, J.; Ruokanen, A.; Keskinen, K. L. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
This study investigated whole-body interlimb coordination in front crawl swimming, focusing on the relationship between upper and lower limb movements. Thirteen competitive swimmers (aged 14-18) performed a 10 x 100 m stepwise test. The swims were recorded above and below water. Coordination patterns were analyzed, assigning values based on the number of inter-connected limbs and mutual timing. Four distinct groups emerged: contralateral, ipsilateral, phasing, and non-coordinated. Contralateral and ipsilateral coordination were the primary patterns. We conclude that the introduction of new coordination indices and comprehensive analysis of coordination groups sheds light on the complexity of movement between the arms and legs during front crawl.